Medium term effects of water availability and N-P fertilization interactions on the productivity and composition of natural grasslands of Uruguay - Jaurena M.; Giorello D.; Cruz P.; Lemaire G.; Nabinger C. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
Irrigation and fertilization could be a strategy to ensure forage production in a high climate variability scenario in Uruguay. Nevertheless, there are gaps in our knowledge of productive and environmental responses. An experiment was performed to evaluate the effects of supplementary irrigation and N-P fertilization on native grassland forage yield and composition from October 2011 to September 2013. First year results showed, under drought, that the interaction between irrigation and N fertilization explains the variations in productivity and composition. Irrigation enhanced N response doubling forage production and the contribution of valuable species. The second year was rainy and forage production was higher than the first one in all treatments. Besides, N-P interaction was detected, explained by an increase on production caused by P mainly at the higher levels of N. These results underline the importance of studying cumulative effects of fertilization and irrigation for a more sustainable grassland management.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)